ANALISIS KEMANDIRIAN PENGELOLAAN KEUANGAN DAERAH KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - MUS MULYADI, B61109041 (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT This research is titled "An Analysis of the Independency in Financial Management in District/City Level of Kalimantan Barat Province". The goal of this research is to analyze the level of local financial independence and the effectiveness of Region's Local Revenue (Pendapatan Asli Daerah/PAD) at the District/City Level in the Province of Kalimantan Barat. Data collected are secondary data from 2007-2010, which were the District/City Level Budget from 2007-2010. The method of research is through quantitative-descriptive analysis which will then be inputted into tables to figure out the level of local financial independency and the effectiveness of Region's Local Revenue (PAD) at the District/City Level in the Province of Kalimantan Barat. The data that is used are time series Budget data (2007-2010) from 14 Districts/Cities in the Province of Kalimantan Barat. The data source that was used is from the Province of Kalimantan Barat's Regional Financial Bureau. The results of the research indicates that: 1) The ratio of local financial independency at the District/City Level in the Province of Kalimantan Barat are around the range of 1,44%-11,74%, which ranks at the category of Lacking and Highly Lacking. This means that the Districts/Cities in the Province of Kalimantan Barat have a high reliance towards external funds to support development of the region. 2) The effectiveness ratio of the Region's Local Revenue (PAD) at the District/City Level in the Province of Kalimantan Barat is still under 100%. This ratio shows that not all Districts/Cities were effectively using the Region's Local Revenue to achieve the targeted development, or what was budgeted at the Regional Budget (APBD). 3) The degree ratio of decentralized fiscal at the District/City Level in the Province of Kalimantan Barat is still very small at the range of 1,42%-10,50%, which is ranked at Lacking and Highly Lacking. This shows that the contribution made by the Region's Local Revenue (PAD) to the total income of the region is miniscule. Key Words: Ratio of Local Financial Independency, Ratio of the effectiveness of Region's Local Revenue (PAD), and the degree ratio of decentralized fiscal.